In vitro EXPRESSION OF INTERLEUKIN-2 AND -10 FROM ALPACA (Vicugna pacos) LEUKOCYTES IN PRESENCE OF CLOSTRIDIAL ANTIGENS - Watanabe W., Raquel (2014)
The aim of the study was to determine the relative in vitro ARNm expression levels of IL-2 and IL-10 in peripheral blood leukocytes by real time RT-PCR and relative quantification using the 2-ΔΔCt method in presence of clostridial antigens and GAPDH as an endogenous control. Whole blood was collected from 10 adult alpacas. Samples were centrifuged to obtain leukocytes using the Ficoll reagent, purified with ammonium chloride and cultured in 24-well plates at a concentration of 500 000 live cells/ml minimal essential medium (MEM) with clostridial extract suspensions at concentrations of 400, 16, 0.8 and 0.2 µg/ml. Subsequently, the RT-qPCR test was performed. IL-2 kinetic expression patterns were inversely proportional to the clostridial antigen dose in the three incubation times (p>0.05), unlike IL-10 which its kinetic expression patterns were variable, reaching its maximum at 12 h (p<0.05) while showing a similar trend like IL-2 in the 16 µg/ml clostridial antigen dose. IL-10 expression exceeded 40-fold the control expression respect to IL-2. A strong polarization towards the Th2 subtype was shown.